The Bar books manuscripts illuminated for Renaud de Bar, Bishop of Metz (1303-1316) - Davenport, Kay 1939- (Manuscripta illuminata, 2017)
This study gives an overview of the man and his books, paying special attention to the heraldry, the calendars, and the marginalia in three appendices. Renaud de Bar (d. 1316) was the sixty-ninth bishop of Metz, and the fourth son of the powerful count of Bar. The house of Bar had a distinguished lineage intertwined with most of the important European houses, and Renaud's eldest brother married the eldest daughter of the king of England. In the last century, as manuscripts were identified and attributed, realisation has gradually dawned that he commissioned six de luxe manuscripts for his particular use in the course of his rapid rise to the episcopacy. The heraldry of his Breviary in two volumes is unique, astonishing in a church book, as it contains about 180 non-Bar shields of arms in two-line initials, in addition to about 225 shields of Bar and Toucy, belonging to his immediate family, and his own personal shield which in the course of the book is scrupulously modified to reflect his elevation to the chair at Metz. This detailed study gives a novel overview of the man and his books, paying special attention to the heraldry, the calendars, and the marginalia in three appendices